Indicators of satisfaction with life in elderly adults in Costa Rica and España - Blanco Molina, Mauricio (2018)
Purpose: The present work explores which are the best indicators of well-being in older people who participate in university programs in Costa Rica and Spain.   Method: A panel design is used to follow the samples on both University Programs, but we only used the first wave of data to the present work.  The samples were built with people 55 plus years old in Spain from the University of Valencia programs (N=652) and in Costa Rica from the National University programs (N=272). We used a questionnaire with different variables:  The Temporal Satisfaction with Life Scale, Lubben Social Network Scale-Revised (LSNS-R), The Duke-UNC Functional Social Support Questionnaire, SF-8 Health Survey, level of social participation, and demographic variables.  We analyzed the data with hierarchical linear regression, correlation coefficients, and descriptive analysis.  Results: All variables measured showed significant correlations with present life satisfaction in both samples. The variables that best predict life satisfaction with a 23% variance explained in the Costa Rican sample were the support network, affective social support and the perceived health. In the Spanish sample, the best model explains 23% of the variance and as predictors have perceived health, social network and social participation.  Conclusions: In both countries, there are significant correlations between life satisfaction, with indicators like support network, social support, perceived health and social participation. We analyze the results contrasting with the predictors of the social participation in old people, lifelong learning, and successful aging models.